O wyrastaniu z pasji - Jaskulska, Sylwia (My University, 2015)
In my paper, I analyse passion in the context of lifelong human development. The main concern is whether passion has to be one and steady, or whether it is possible to have various passions in life, or even many different passions at the same time? To answer my question, I refer myself to the psychology of human development and the psychology of interests, as well as to Robert J. Vallerand’s dualistic model of passion.
About growing out of passion
Keywords: passion; development; psychology of interests